Trabecular Bone Score: From Over a Decade of Evidence to a Connected Bone Health Ecosystem - Hind, Karen; Davies, Madeleine; Gonzalez-Rodriguez, Elena; Hans, Didier (Osteologie, 2025)
Effective assessment of bone health requires evaluation of both bone mass and bone microarchitecture. Osteoporosis is characterised not only by reduced bone mineral density (BMD) but also by deterioration of trabecular microstructure, both of which contribute independently to fracture risk. Despite this, clinical evaluation often focuses solely on BMD, which fails to capture many individuals at risk. Indeed, the majority of fragility fractures occur in patients with BMD values above the osteoporotic threshold, underscoring the importance of incorporating additional measures of bone quality. Trabecular bone score (TBS) is a validated, non-invasive index of bone microarchitecture derived from lumbar spine DXA images. By providing complementary and additive information, TBS improves the detection of individuals at elevated fracture risk who may be missed by BMD alone. For more than a decade, TBS has been extensively validated as an independent predictor of fracture risk, for both the assessment and management of osteoporosis. This article reviews the clinical evidence supporting TBS and its integration into routine practice. We also introduce a broader vision for future connected bone health ecosystem, in which next-generation TBS solutions, including TBS Reveal™ for opportunistic screening from X-rays and TBS Ortho™ for pre-operative fragility assessment, expand the clinical reach of bone quality assessment. Together, these technologies provide scalable, AI-enabled tools to support precision bone fragility evaluation across diverse clinical settings and patient populations.
Keywords: trabecular bone score; bone microarchitecture; fracture risk assessment; osteoporosis diagnostics